2020
DOI: 10.3389/fcimb.2020.00393
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Genetic Discoveries in the Skin Commensal and Pathogenic Malassezia Yeasts

Abstract: Malassezia includes yeasts belong to the subphylum Ustilaginomycotina within the Basidiomycota. Malassezia yeasts are commonly found as commensals on human and animal skin. Nevertheless, Malassezia species are also associated with several skin disorders, such as dandruff/seborrheic dermatitis, atopic eczema, pityriasis versicolor, and folliculitis. More recently, associations of Malassezia with Crohn's disease, pancreatic ductal adenocarcinoma, and cystic fibrosis pulmonary exacerbation have been reported. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
(107 reference statements)
2
8
0
Order By: Relevance
“…Previous phylogenetic analysis conducted by Honnavar et al as well as other previous analyses using D1/D2 domains of large subunit (LSU) ribosomal DNA (rDNA) sequences showed that M. globosa , M. restricta , and M. arunalokei are closely clustered within the same clade in the phylograms ( 1 , 2 , 9 ), and our result was in accordance with these findings. However, we also observed two distinct subspecies groups in the M. restricta species ( M. restricta CBS 8741 and KCTC 27527 versus M. restricta CBS 7877) in the phylogram we generated.…”
Section: Resultssupporting
confidence: 92%
“…Previous phylogenetic analysis conducted by Honnavar et al as well as other previous analyses using D1/D2 domains of large subunit (LSU) ribosomal DNA (rDNA) sequences showed that M. globosa , M. restricta , and M. arunalokei are closely clustered within the same clade in the phylograms ( 1 , 2 , 9 ), and our result was in accordance with these findings. However, we also observed two distinct subspecies groups in the M. restricta species ( M. restricta CBS 8741 and KCTC 27527 versus M. restricta CBS 7877) in the phylogram we generated.…”
Section: Resultssupporting
confidence: 92%
“…have been isolated from mammals' skin. 22 Conventional culture-based studies showed that M. globosa and M. restricta were the predominant species in SD patients. 23 Disequilibrium in the ratio of M. restricta/M.…”
Section: Lin Et Al (2020)mentioning
confidence: 99%
“…A series of horizontal gene transfers have been defined and further cloud the phylogeny ( Ianiri et al., 2020 ). For example, another recent LSU tree, while very similar implies different grouping and relationships ( Ianiri and Heitman, 2020 ). These findings highlight that while much has been learned about Malassezia phylogeny there is still a long way to go to understanding this unusual clade.…”
Section: Malassezia : a Major Component Of The Skin Microbiomentioning
confidence: 99%
“…Historically, Malassezia genetic engineering has been extremely challenging. However, it has now been accomplished via agrobacterium-mediated transformation ( Ianiri et al., 2016 ; Celis et al., 2017 ; Ianiri and Heitman, 2020 ). For example, gene deletion of a bacterially derived flavohemoglobin gene found in all Malassezia spp.…”
Section: Malassezia : a Major Component Of The Skin Microbiomentioning
confidence: 99%